2019
DOI: 10.1021/acs.oprd.9b00247
|View full text |Cite
|
Sign up to set email alerts
|

Improving Powder Characteristics by Surface Modification Using Atomic Layer Deposition

Abstract: The particulate properties of a material after primary manufacturing have a large impact on the secondary manufacturing processes. Especially, powder characteristics leading to poor flowability are critical and need to be controlled at the late steps of primary operations. The surface properties of the primary particles are hereby one of the determining factors for the behavior of particulate systems. Materials with different particulate properties were coated using atomic layer deposition (ALD) to apply an ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…Widely used for the functionalization of wafers in the semiconductor industry with oxide ceramic films, ALD has also been applied to a large variety of powders, recently also including pharmaceutical particles, due to its ability to conformally coat complex three-dimensional substrates. Crucially, nanophase ceramics have already been used in a broad spectrum of biomedical and drug delivery applications, as they can modulate drug release kinetics, incorporate multifunctional molecules, and target action sites . ALD of oxide ceramics can therefore extend release and improve flow properties and solid-state stability of virtually any pharmaceutical substance. , Nanoscale oxide ceramic ALD films have been shown to slow down the dissolution rate of acetaminophen particles, while preventing drug chemical degradation and cytotoxicity . Similarly, we have demonstrated that nanosized Al 2 O 3 -based films grown via ALD in a fluidized bed reactor at nearly ambient conditions can greatly sustain the release and improve the dispersibility of budesonide and lactose particles. , In addition, Al 2 O 3 ALD films with a thickness of 30–35 nm have been proven to maintain a stable plasma concentration for indomethacin, when administered subcutaneously in rats, up to over 12 weeks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely used for the functionalization of wafers in the semiconductor industry with oxide ceramic films, ALD has also been applied to a large variety of powders, recently also including pharmaceutical particles, due to its ability to conformally coat complex three-dimensional substrates. Crucially, nanophase ceramics have already been used in a broad spectrum of biomedical and drug delivery applications, as they can modulate drug release kinetics, incorporate multifunctional molecules, and target action sites . ALD of oxide ceramics can therefore extend release and improve flow properties and solid-state stability of virtually any pharmaceutical substance. , Nanoscale oxide ceramic ALD films have been shown to slow down the dissolution rate of acetaminophen particles, while preventing drug chemical degradation and cytotoxicity . Similarly, we have demonstrated that nanosized Al 2 O 3 -based films grown via ALD in a fluidized bed reactor at nearly ambient conditions can greatly sustain the release and improve the dispersibility of budesonide and lactose particles. , In addition, Al 2 O 3 ALD films with a thickness of 30–35 nm have been proven to maintain a stable plasma concentration for indomethacin, when administered subcutaneously in rats, up to over 12 weeks .…”
Section: Introductionmentioning
confidence: 99%
“…However, neither in vitro nor ex vivo biorelevant studies of ALD-coated inhaled drugs have been reported yet. Moreover, the effect of the ALD films on drug dissolution and other functional properties such as flowability is not well understood. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…One method for mitigating this drawback of using Si is to coat the Si-based anode with various materials, which suppress the volume expansion and prevent direct contact with the electrolyte [32,33]. Various methods such as wet coating, physical vapor deposition, chemical vapor deposition (CVD), and atomic layer deposition (ALD) are employed to coat the anode with a suitable material [34,35]. Among them, the wet coating method is relatively simple but has the disadvantage of a low diffusion rate, and the final product may show poor homogeneity according to the mixing energy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the coating methods, atomic layer deposition (ALD) [24–28] is ideal for producing thin films with a controllable, conformal and uniform design by sequential self‐limited reactions. Previous works have demonstrated ALD as a viable technique to modify electrodes with different inorganic metal oxides thin films, [29–33] including Al 2 O 3 , TiO 2 , and ZrO 2 thin film coatings. Such ALD thin films are used as an artificial solid electrolyte interphase (ASEI) that improves the electrodes stability enhances their electrochemical performance [34] …”
Section: Introductionmentioning
confidence: 99%